First line anti-tubercular drug resistance among patients visiting German Nepal Tuberculosis Project, Nepal - Regmi, S; Shrestha, B; Katuwal, A (International Journal of Infection and Microbiology, 2013)
INTRODUCTION: Tuberculosis is one of the commonest causes of death in the world. It remains a major public health problem in developing countries including Nepal. Despite the reduction in incidence of tuberculosis by the implementation of anti-tuberculosis drugs regimen, TB remains pandemic due to emergence of drug resistant strain of M. tuberculosis. The aim of this study was to evaluate the first line anti-tubercular drug resistance among patients visiting German Nepal Tuberculosis Project, Nepal. MATERIALS AND METHODS: Anti-tubercular drug susceptibility test for first line drugs (Rifampicin, Isonizid, Ethambutol, and Streptomycin) was performed by proportion method (n=141) for new sputum smear positive patients attending German Nepal Tuberculosis Project, Kathmandu, Nepal. RESULTS: 78.1% (n=110.) were sensitive to all 4 drugs. Eight isolates (5.6%), 4(2.8%), 10(7.1%) and 31(21.9%) were resistant to any 4, 3, 2 and 1 drug respectively. Proportion of drug resistant (PDR) to one drug was 12.6%, two drugs 7.6%, three drugs (6.3%) and four drugs was 5.6%. Our result indicates the PDR to the first line drug was 21.9% and multidrug resistant (MDR) was 12 (8.5%). CONCLUSIONS: Drugs resistant cases of tuberculosis in increasing. Surveillance and monitoring of the drug resistant tuberculosis is necessary to prevent emergence of MDR, extensively drug resistant and so-called totally drug resistant tuberculosis. DOI: http://dx.doi.org/10.3126/ijim.v2i2.8321 Int J Infect Microbiol 2013;2(2):45-48